The use of Holocene bovid fossils to infer palaeoenvironment in Africa - (:unkn) unknown (My University, 2006)
In this paper, we develop an original statistical method to infer palaeoenvironmental conditions from fossil taxonomical assemblages based on the present-day observed environmental characteristics of these taxa. We illustrate this method by analysing present-day and Holocene African bovid (Artiodactyla, Mammalia) species assemblages. Firstly, the modern bovid species occurrences in African environments ranging from tropical rainforest to desert are compiled in order to define the environmental characteristics of each species analysed. Secondly, these modern characteristics are considered in order to construct a statistical model of prediction of actual environmental conditions from the sets of most likely environments associated with each present-day location (station). The model then allows us to infer palaeoenvironmental conditions associated with archaeozoological evidence of 53 Holocene localities from Western Africa. Our results show that a tree cover was well established near rivers and uplands, and constituted refuge areas for human occupation during times of climatic desiccation. This conclusion is discussed in the climatic, environmental and archaeological contexts of the Holocene evolution and prehistory of Western Africa.
Keywords: African Research